Financial information system at krustyzone playground based on android - Safari Nurliana; Leon A. Abdillah; Nyimas Sopiah; Taqrim Ibadi (Universitas Mercu Buana Yogyakarta, 2025)
The development of information technology encourages the need for efficient and mobile systems, especially in the small business sector such as playgrounds. This research aims to design and develop an Android-based Financial Information System at Krustyzone Playground to overcome the obstacles of manual recording, report delays, and lack of real-time data. The method used is Rapid Application Development (RAD), which allows a fast development process through design iterations and direct feedback from users. The system was developed using the CodeIgniter framework and MySQL database, and modeled with UML (Use Case Diagram, Activity Diagram, and Class Diagram). The implementation results show that the system is able to record income and expenses, display real-time financial reports, and manage users with different access rights. Tests through the Black Box Testing method prove that all functions run as expected. Validation by users shows the application is easy to use, efficient, and responsive. In conclusion, this system supports more accurate, secure, and structured financial management, as well as being an appropriate technology solution in assisting businesses in making decisions based on actual data.